SISTEM INFORMASI CUCI SEPATU BERBASIS WEBSITE (STUDI KASUS NOSTAINSSHOES) - Agustiyanto, Rizky Dwi; -, Dahlan (Jurnal Mahasiswa Terapan, 2024)
The Shoe Cleaning Information System is a solution designed to facilitate the recording and management of shoe cleaning services. The system was developed using various analytical and modeling methods such as Use Case Diagrams, Activity Diagrams, Sequence Diagrams, and ERD to create an effective framework. The system also includes a user interface designed for easy user interaction. The waterfall method was employed as the development methodology, while testing was conducted using Blackbox and User Acceptance Test (UAT) methods. The test results show that all system functions operate as expected, and UAT results indicate a user acceptance rate of 86.80%. Therefore, the Shoe Cleaning Information System is well-received by users and provides an efficient solution for recording and managing shoe cleaning services.